Spatiotemporal Variations in Chemical Composition of Wet Atmospheric Deposition in Mexico City - Elizabeth Vega; Ann Wellens; Ana Luisa Alarcón; Rodolfo Sosa; Monica Solano; Monica Jaimes-Palomera (Aerosol and Air Quality Research)
Abstract A comprehensive analysis of the chemical composition of wet atmospheric deposition was performed on 7048 samples collected between 2003 and 2021 over Mexico City. The descending ion abundance trend was NH4+ > SO42− > NO3− > Ca2+ > Cl− > H+ > Mg2+ > Na+ > K+, probably associated with industrial activity, heavy traffic and agricultural activities. Although main precursors have decreased importantly, ion composition did not show a clear trend throughout the years. Maximum concentrations of major ions were found in the northern and central part of the megacity, due to the impact of the Tula industrial corridor located north of the city. Weekly pH values varied from 3.6 to 9.4, being 27.1% of the values acidic. Fractional acidity showed that in sites located at higher altitudes, maximum 84.5% of the acidity was neutralized, whereas at northern stations at lower altitudes neutralization was observed up to 98%, due to the presence of alkaline species coming from the cement industry. Average ratios of (NH4+ + Ca2+)/(NO3− + SO42−) were > 1, suggesting neutralization of SO42− and NO3− by NH4+ and Ca2+. Average NO3−/SO42− ratios suggested that the acidity was mainly influenced by sulfates coming from H2SO4. Wet deposition ranged from 4–9.9 kg ha−1 year−1 and from 8.2–17.6 kg ha−1 year−1 for sulfur and nitrogen, respectively, among the geographical areas. The results of this study highlight the sensitivity of wet deposition chemistry to geographical, elevation and source considerations.